PMO-182 HCV research UK: a UK national resource to support research into HCV infection. (28th May 2012) - Irving, W; McLauchlan, J; Foster, G; Dillon, J; Hutchinson, S; Wilkes, B
Abstract : Introduction: Background: Hepatitis C virus (HCV) infection has been identified by the MRC and Department of Health MRC as a priority area for research and development to meet the clinical challenges posed by the scale of the infection in the UK. There has been a perceived lack of connection between clinicians and basic scientists working on HCV in the UK to address this problem. Aims: To create a multi-disciplinary consortium comprising clinicians and non-clinical scientists to encourage translational research. To establish a cohort of 10 000 patients with HCV infection across the UK, together with clinical database and biorepository—"HCV Research UK". To make this resource available to researchers, both academic/commercial, UK-based and abroad. Methods: Aims: Our objective has been to create a multi-disciplinary consortium comprising clinicians and non-clinical scientists to encourage translational research into the factors that determine outcome of infection, treatment response and disease progression. We aim to establish a cohort of 10 000 patients with HCV infection from across the UK that is supported by the necessary systems to make clinical data and specimens available to academic and commercial researchers, both in the UK and abroad. Results: Progress: HCV Research UK has been funded by the Medical Research Foundation (£1.92 million) to establish an infrastructure that connects 18 clinical centres who will recruit 10 000 HCV-infected patients. The key elements of the infrastructure are a bespoke clinical research database, which is linked to a biorepository of samples that will hold serum, PBMCs and DNA from patients. Access to data and samples is managed by a Tissue and Data Access Committee who have the authority to grant ethical approval for research using the resource. The study has been given CLRN portfolio status. Conclusion: Future plans: Recruitment of patients will begin in early 2012 and grant applications have been submitted to (1) Wellcome/Department of Health Innovation Challenge fund (2) MRC call for Stratified Medicine (3) BLT Research call (4) NIHR Programme Development award schemes for research using the resource. It is hoped that portfolio support will provide a mechanism for new centres to join the consortium. Competing interests: None declared.